River of darkness : Francisco Orellana's legendary voyage of death and discovery down the Amazon - Levy, Buddy, 1960- (Bantam Books, 2011)
From the acclaimed author of "Conquistador" comes this thrilling account of one of history's greatest adventures of discovery--the true story of a legendary sixteenth-century explorer and his death-defying navigation of the Amazon.